PENGGUNAAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR KELAS XII IPA 1 SEKOLAH MENENGAH ATAS NEGERI 1 PETANG - Widani, Ni Ketut (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2017)
This research was conducted in SMA N 1 Petang in odd semester of 2013/2014 School Year. Class Action Research has been carried out from the problem that is: the low motivation and study result of Reaction Redox Basic Competence (KD) in previousyears of first semester of Class XII IPA students. Class XII IPA 1 selected, as research subject with the objects of research are the motivation and learning achievements. With success criteria: â‰¥ Minimum Exhaustiveness Criteria (KKM). The set up KKM is 75; Absorption Power (DS) of at least 75%; Classic completeness (KK) of at least 80%; Motivation â‰¥ 66.17. The results showed that the use of Audiovisual Media can improve the motivation and learning outcomes of students with average learning motivation 77.06 and average learning outcomes (X) = 77.03 Absorption = 77.03% Classical Exhaustion (KK) = 81, 15. This shows that the use of audiovisual media can improve the motivation and learning outcomes of Class XII IPA 1 Odd semester students of 2013-2014 School Year on Redox Reaction Basic Competence.